Impact of worker demographics and shift rotation on work stress factors in manufacturing - Bugvi, Salman Abubakar; Hameed, Khurram; Hussain, Amjad; Ahmad Mufti, Nadeem; Ahmad, Aftab; Jamil, Fawad; Ghauri, Farooq (Penerbit Universiti Kebangsaan Malaysia, 2022)
Work Stress is a barrier towards productivity and efficiency in manufacturing sector. Various factors of stress interact with the demographics such as age, education, experience, marital status and smoking habits of workers. Different workers exhibit different reactions towards work stress. To enhance productivity, manufacturing industry is utilizing night shift. However, night shift work is against the natural tendency of humans. The impact of rotating shift in context of work-stress of the workers is an area of concern. To understand the impact of demographics and shift rotation on work-stress of the workers, a quantitative study was undertaken in a medium sized automotive organization. The case organization was explored through a survey questionnaire administered to both day and night shift workers and analysed through Non parametric Spearman correlation and Mann Whitney U Test. The study highlights the need for effective reward and gratification scheme (Young Worker Avg 3.12 – Old Worker Avg 3.82), taking care of old age workers (Muscle Pain Old Avg 4.47 – Young Avg 3.84), reducing the smoking habit (Depression Smoking Avg 3.79 – Non Smoking Avg 3.12) (Fatigue Smoking Avg 3.92 – Non Smoking Avg 3.06), fostering social community and teamwork. Night shift may enhance production but should not be accepted as an ideal solution. The downsides and ill effects of the unnatural night shift work in the form of work stress are identified and should be reduced by management.